2016
DOI: 10.1103/physrevlett.116.255003
|View full text |Cite
|
Sign up to set email alerts
|

Low Fuel Convergence Path to Direct-Drive Fusion Ignition

Abstract: A new class of inertial fusion capsules is presented that combines multishell targets with laser direct drive at low intensity (2.8 × 10 14 W=cm 2 ) to achieve robust ignition. The targets consist of three concentric, heavy, metal shells, enclosing a volume of tens of μg of liquid deuterium-tritium fuel. Ignition is designed to occur well "upstream" from stagnation, with minimal pusher deceleration to mitigate interface Rayleigh-Taylor growth. Laser intensities below thresholds for laser plasma instability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…In inertial confinement applications (ICF), [5][6][7] beryllium has been used as an ablator for indirect-drive fuel capsule designs [8][9][10][11] because of its advantages of high density, low opacity, high thermal conductivity, 12 and low instability growth. 13,14 Since these target designs are based mainly on the radiation-hydrodynamic simulations where the materials will experience many different pressures (up to 10 5 Mbar) and temperature (up to 10 8 K) conditions, 15 accurate properties of beryllium under such extreme conditions are essential for ICF applications. Experimental data are limited to 20 Mbar, however, because of the difficulty in generating shocks and measuring them accurately.…”
Section: Introductionmentioning
confidence: 99%
“…In inertial confinement applications (ICF), [5][6][7] beryllium has been used as an ablator for indirect-drive fuel capsule designs [8][9][10][11] because of its advantages of high density, low opacity, high thermal conductivity, 12 and low instability growth. 13,14 Since these target designs are based mainly on the radiation-hydrodynamic simulations where the materials will experience many different pressures (up to 10 5 Mbar) and temperature (up to 10 8 K) conditions, 15 accurate properties of beryllium under such extreme conditions are essential for ICF applications. Experimental data are limited to 20 Mbar, however, because of the difficulty in generating shocks and measuring them accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation hydrodynamic simulations are used to indicate the duration of validity of the model as the coronal plasma expands and to evaluate the ablative properties for large spherical targets. It is found that the planar model can be appropriately applied to a 3.1 mm radius capsule, similar to the one encountered in the Revolver target baseline design 3 , early in the laser pulse. The recovery of planar ablation scaling early in time is attributed to the length scale of the rarefied coronal plasma being small compared to the target radius.…”
Section: Normal Incidencementioning
confidence: 91%
“…Polar direct drive (PDD) is the only near-term viable method for driving a variety of proposed direct drive ignition target designs (see Refs. [1][2][3][4] on the National Ignition Facility (NIF). In its current indirect drive configuration, NIF's 192 laser beams emanate from laser ports at angles of 23.5, 30, 44.5, and 50 degrees from the poles of its spherical target chamber.…”
Section: Introductionmentioning
confidence: 99%
“…Directly-driven large capsules tested their applicability for the Revolver tripleshell ignition capsule [116] and for plasma kinetic studies. The Revolver concept uses a very large outer shell, 6-mm diameter, to initiate the implosion.…”
Section: Direct-drive Platformsmentioning
confidence: 99%
“…Recent experiments investigating the Revolver concept of triple-shell implosions [116,128] tested the concept of launching very large, low-velocity Be shells at Omega [119].These experiments showed that a 1.2-mm-diameter, 15-µm-thick, Be shell could be accelerated to a velocity of 7.5 cm/µsec as opposed to the usual single-shell ignition design velocity of 35 cm/µsec [119]. These experiments did not use a gas fill.…”
Section: 2 Metal Capsulesmentioning
confidence: 99%